A qualidade percebida e o perfil dos egressos da Faculdade de Agronomia em uma instituição de ensino superior - Cabral, Ana Beatriz Ferreira Peres (Universidade do Vale do Rio dos Sinos, 2024)
Perceived value is a crucial concept for understanding student satisfaction and the quality of a Higher Education Institution (HEI). In this study, we assessed the opinions of graduates who completed their studies between 2019 and 2022 at the Agronomy College of an HEI in Goiás, recognizing its importance for educational management in the face of social and market changes. The interaction between the course director and graduates is essential to ensure that education aligns with market realities and fosters meaningful exchange. We employed a quantitative and qualitative approach through a case study, collecting data via an online questionnaire. We identified positive aspects and key needs perceived by graduates, aiming for a clear understanding of the College. Results highlight a positive perceived value, emphasizing the institution's comprehensive student education and continual course updates to meet market demands.
Keywords: Egressos; Satisfação; Qualidade; Expectativas; Formação; Ensino superior; Graduates; Satisfaction; Quality; Expectations; Training; Higher education; ACCNPQ::Ciências Sociais Aplicadas::Administração